Weight stigma in maternity care: women's experiences and care providers' attitudes - Mulherin Kate; Miller Yvette D; Barlow Fiona Kate; Diedrichs Phillippa C; Thompson Rachel (BMC, 2013)
Abstract Background Weight stigma is pervasive in Western society and in healthcare settings, and has a negative impact on victims' psychological and physical health. In the context of an increasing focus on the management of overweight and obese women during and after pregnancy in research and clinical practice, the current studies aimed to examine the presence of weight stigma in maternity care. Addressing previous limitations in the weight stigma literature, this paper quantitatively explores the presence of weight stigma from both patient and care provider perspectives. Methods Study One investigated associations between pre-pregnancy body mass index (BMI) and experiences of maternity care from a state-wide, self-reported survey of 627 Australian women who gave birth in 2009. Study Two involved administration of an online survey to 248 Australian pre-service medical and maternity care providers, to investigate their perceptions of, and attitudes towards, providing care for pregnant patients of differing body sizes. Both studies used linear regression analyses. Results Women with a higher BMI were more likely to report negative experiences of care during pregnancy and after birth, compared to lower weight women. Pre-service maternity care providers perceived overweight and obese women as having poorer self-management behaviours, and reported less positive attitudes towards caring for overweight or obese pregnant women, than normal-weight pregnant women. Even care providers who reported few weight stigmatising attitudes responded less positively to overweight and obese pregnant women. Conclusions Overall, these results provide preliminary evidence that weight stigma is present in maternity care settings in Australia. They suggest a need for further research into the nature and consequences of weight stigma in maternity care, and for the inclusion of strategies to recognise and combat weight stigma in maternity care professionals' training.